Avaliação de modelo tridimensional não invasivo da articulação coxofemoral em ovinos hígidos - Agostinho, Felipe Stefan [UNESP] (2015)
The aim of this study was to develop and evaluate a noninvasive three-dimensional model of the hip joint in sound sheep using a joint coordinate system, and to compare and correlate it with two sagittal models. Eight sound sheep of similar size, intact, female, aged from 2 to 4 years were used. Three models were used to angle calculations including joint coordinate system (SCA), and sagittal linear (MSL) and sagittal segmental model (MSS). The SCA, MSL and MSS models were able to capture flexion/extension and abduction/adduction angles whereas SCA model also was able to capture internal/external rotation angle. Maximum angle, minimum angle and angular displacement were calculated for all variables. Comparing SCA to MSL, significant differences were not observed. Differences were observed in all comparisons between SCA/MSS and MSL/MSS, except for flexion/extension displacement between SCA/MSS that was similar. The values of internal/external rotation angles showed high variability. The correlations were significant for both flexion/extension and abduction/adduction angles in the three models, except for abduction/adduction displacement between MSL/MSS. In conclusion, the flexion/extension and abduction/adduction angles obtained with joint coordinate system were similar to sagittal linear, but not with sagittal segmental model. The internal/external rotation angle data obtained by joint coordinate system may not be useful